Cote d'Ivoire : 2021 Article IV Consultation-Press Release; Staff Report; Informational Annex; Debt Sustainability Analysis; Selected Issues; and Statement by the Executive Director for Cote d'Ivoire. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2022)
Cote d'Ivoire has shown strong resilience to the pandemic, owing to the authorities' swift policy reaction and to a decade of sound macroeconomic policies, as well as the support of the international community including the IMF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: China, People's Republic of